2015
DOI: 10.1016/j.ebcr.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Disabling amnestic syndrome following stereotactic laser ablation of a hypothalamic hamartoma in a patient with a prior temporal lobectomy

Abstract: A 19-year-old man with cortical dysplasia and intractable focal seizures underwent a right temporal lobectomy. A hypothalamic hamartoma was subsequently recognized, and he then underwent MRI-guided stereotactic laser ablation. Unfortunately, he sustained damage to the bilateral medial mammillary bodies and suffered significant memory loss. We review laser ablation therapy for hypothalamic hamartomas and the anatomy of the memory network. We postulate that his persistent memory disorder resulted from a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…A major advantage of SRS in treating intracranial advantage is its avoidance of intraoperative complications. However, it achieves rates of cure in HH cases that appear to be lower than in LITT, and symptomatic postoperative radiation‐related edema is a known risk . Furthermore, the 12‐to 18‐month latency to therapeutic effect would carry consequences relevant to children, potentially limiting the developmental future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major advantage of SRS in treating intracranial advantage is its avoidance of intraoperative complications. However, it achieves rates of cure in HH cases that appear to be lower than in LITT, and symptomatic postoperative radiation‐related edema is a known risk . Furthermore, the 12‐to 18‐month latency to therapeutic effect would carry consequences relevant to children, potentially limiting the developmental future.…”
Section: Discussionmentioning
confidence: 99%
“…However, it achieves rates of cure in HH cases that appear to be lower than in LITT, and symptomatic postoperative radiation-related edema is a known risk. 39 Furthermore, the 12-to 18-month latency to therapeutic effect would carry consequences relevant to children, potentially limiting the developmental future. It can nevertheless be an effective tool used in conjunction with LITT and other modalities to approach HH pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Real tissue damage, however, is produced by ablation and, the risk of permanent neurological deficits should be considered. A prior case report described disabling amnestic syndrome after laser ablation of a hypothalamic hamartoma, resulting from injury to the mammillary bodies in a patient with prior right temporal lobectomy …”
Section: Discussionmentioning
confidence: 99%
“…A prior case report described disabling amnestic syndrome after laser ablation of a hypothalamic hamartoma, resulting from injury to the mammillary bodies in a patient with prior right temporal lobectomy. 15 Case 3 patient has been followed for 19 months. She had one seizure after the procedure which may have been triggered by infection and two other episodes since then, which were brief (prior to surgery, frequency was 1-2 seizures/week).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, safety was excellent with one patient experiencing an asymptomatic subarachnoid hemorrhage, and with a median length of stay of 1 day. Zubkov et al reported a single case of a disabling amnestic syndrome following laser ablation of a HH in a 19-year old with a prior right temporal lobectomy (118). Post-ablation imaging showed edema in the bilateral mammillary bodies, which likely contributed to the deficit, although the role of the prior lobectomy is uncertain.…”
Section: Clinical Outcomes Using Commercial Mriglittmentioning
confidence: 99%